Governance explains variation in national responses to the biodiversity crisis. (13th February 2018) - BAYNHAM-HERD, ZACHARY; AMANO, TATSUYA; SUTHERLAND, WILLIAM J.; DONALD, PAUL F.
SUMMARY: Growing concern about the biodiversity crisis has led to a proliferation of conservation responses, but with wide variation between countries in the levels of engagement and investment. Much of this variation is inevitably attributed to differences between nations in wealth. However, the relationship between environmentalism and wealth is complex and it is increasingly apparent that other factors are also involved. We review hypotheses that have been developed to explain variation in broad environmentalism and show that many of the factors that explain such variation in individuals, such as wealth, age and experience, also explain differences between nation states. We then assess the extent to which these factors explain variation between nation states in responses to and investment in the more specific area of biodiversity conservation. Unexpectedly, quality of governance explained substantially more variation in public and state investment in biodiversity conservation than did direct measures of wealth. The results inform assessments of where conservation investments might most profitably be directed in the future and suggest that metrics relating to governance might be of considerable use in conservation planning.